Managerial Approach in Implementing Management Accounting During Corporate Crisis at PT Lisna Syifa’ Prima - Ikhsan, Andi muh ikhsan s alwi; Arifuddin; Syarifuddin (CITACONOMIA, 2025)
Financial crises in the pharmaceutical distribution sector often generate complex managerial challenges that test organizational adaptability and resilience. This study investigates the managerial approaches used in implementing Management Accounting Systems (MAS) during a severe corporate financial crisis at PT Lisna Syifa’ Prima, a leading pharmaceutical distributor in Indonesia. The crisis, triggered by prolonged payment delays from APLN (a major health insurance provider linked to PLN), led to severe cash flow disruptions, supplier payment deferrals, operational slowdowns, and heightened insolvency risks. Employing a qualitative case study methodology, this research relies on semi-structured interviews with key informants—including the CEO, finance manager, operations manager, and accounting staff—supplemented by direct observations from financial strategy sessions and archival reviews of documents such as cash flow statements, supplier invoices, liquidity reports, and internal audits. The analysis reveals that adaptive and participative leadership styles were instrumental in deploying MAS effectively, fostering data-driven decision-making for liquidity forecasting, expense prioritization, and cross-functional collaboration. MAS tools enabled scenario simulations, cost optimization, and real-time monitoring, which ultimately mitigated the crisis and supported recovery. However, challenges like outdated IT infrastructure, siloed data systems, and limited analytical skills among employees hindered full MAS potential, delaying agile responses. Drawing on contingency theory, this paper extends the literature by illustrating how leadership dynamics and technological factors moderate MAS performance in crisis settings. Practically, it recommends pharmaceutical firms invest in integrated digital platforms, employee training in data analytics, and leadership programs emphasizing agility. Ultimately, the study underscores that in turbulent economic environments, robust MAS integration under adaptive management is vital not just for survival but for fostering long-term organizational sustainability and competitive edge.